Short Hairpin RNAs for Strand-Specific Small Interfering RNA Production - Sheng, Peike; Flood, Krystal A.; Xie, Mingyi (Frontiers in Bioengineering and Biotechnology, 2020)
RNA interference (RNAi) is an effective mechanism for inhibiting gene expression at the post-transcriptional level. Expression of a messenger RNA (mRNA) can be inhibited by a ~22-nucleotide (nt) small interfering (si)RNA with the corresponding reverse complementary sequence. Typically, a duplex of siRNA, composed of the desired siRNA and a passenger strand, is processed from a short hairpin RNA (shRNA) precursor by Dicer. Subsequently, one strand of the siRNA duplex is associated with Argonaute (Ago) protein for RNAi. Although RNAi is widely used, the off-target effect induced by the passenger strand remains a potential problem. Here, based on current understanding of endogenous precursor microRNA (pre-miRNA) hairpins, called Ago-shRNA and m7G-capped pre-miRNA, we discuss the principles of shRNA designs that produce a single siRNA from one strand of the hairpin